(untitled) (Current Horticulture, 2024)
An experiment was conducted to find out the effect of biofertilizers and growing media on growth of air-layers of pomegranate (Punica granatum L.) var. Bhagwa at College of Horticulture, Jagudan during kharif, 2021 in FCRD with three repetitions. It consists of two levels of biofertilizers along with five levels of media mixtures by volume basis. The B1G5 (Bio NPK consortium + soil + FYM + vermicompost (1:1:1, v/v/v)) was found significantly superior for number of new shoots (5.40 and 5.47), length of layer (53.41 cm and 55.25 cm) and number of leaves (117.61 and 127.40) at 60 and 75 DAP, respectively. Similar trends were also noted in the same treatment with respect to fresh and dry weight of shoot (14.88 g and 3.89 g, respectively) at 75 DAP.